Symbols of fear in pandemics: a Kristevan analysis of COVID-19 symbols and power relations in Indonesia - Eko Nugroho; Devi Tri Indriasari; Karman Karman; Amri Dunan; Makroen Sanjaya; Bambang Mudjiyanto; Rukman Pala; Syarifuddin Syarifuddin; Muhammad Rustam (Cogent Arts & Humanities)
This study investigated the intricate interplay of fear, knowledge, and power in shaping pandemic narratives, focusing specifically on the COVID-19 crisis through historical intertextuality and genealogy. Drawing upon Kristeva’s concept of intertextuality and Foucault’s genealogical approach, the research analysed recurring patterns in constructing and disseminating knowledge surrounding disease outbreaks from the Plague of Athens to the present day. Through examining symbols of fear across economic, political, and cultural-religious dimensions, the study revealed how pandemics have consistently served as arenas for power struggles, scapegoating, and ideological control. The COVID-19 pandemic, unfolding in a hyper-connected world characterized by globalized information systems and pervasive social media, amplified these historical dynamics, accelerating the spread of both fear and misinformation. Furthermore, the study traced the evolution of societal responses to pandemics, from the fatalistic acceptance prevalent in earlier eras to the contemporary recognition of human agency, now intertwined with digital networks and algorithmic control. Ultimately, this research underscored the enduring and complex relationship between fear, knowledge, and power, offering critical insights into pandemics’ societal and ethical challenges. By situating COVID-19 within a broader historical context, this study advocated for a more equitable and compassionate global response to future health crises.